Optimalisasi Penggunaan Pupuk Kompos dengan Penambahan Effective Microorganism 10 (Em10) pada Produktivitas Tanaman Jagung (Zea mays L.) - Elpawati Elpawati; Stephani Dwi Dara; Dasumiati Dasumiati (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2015)
This research is aimed to determine the effect of growing media composition, the addition different concentration of EM10 fertilizer, and interaction between the composition of the growing media with different concentration of EM10 fertilizer on Zea mays growth and productivity. This research was conducted in Home Composting of UIN Syarif Hidayatullah Jakarta from June until October 2013. This study used Random Grouped for Factorial Design 2 x 5 wth 3 repetitions. First factor was plant media dose (M), consist of two extents, M1 (compost:soil = 1:1) and M2 (compost:soil = 1:2). The second factor was fertilizer concentration (D), consist of five extents, DO (no fertilizer),D1 (Urea: 0,9 g, SP-36: 0,9 g, KCl: 0,45 g), D2 (10 ml EM10), D3 (15 ml EM10), and D4 (20 ml EM10). The obtained data was analyzed using Analysis of Varians(ANOVA) and Duncan test when there is a significant difference..The result showed plant media (M2) with ratio composition of compost and soil was 1:2 could increase the stem diameter at harvest time. 20 ml concentration of EM10 could increase the stem diameter’s growth (2.29 mm) at harvest time, similarly 15 ml EM10 could increase the cob’s productivity (1.66 cobs). The interaction of composition plant media and fertilizer concentration of EM10 did not influence corn’s growth and productivity.